2015
DOI: 10.1155/2015/215761
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Hypoxia Inducible Factor‐1α and Vascular Endothelial Growth Factor in Pulp Tissue of Teeth under Orthodontic Movement

Abstract: Orthodontic force may lead to cell damage, circulatory disturbances, and vascular changes of the dental pulp, which make a hypoxic environment in pulp. In order to maintain the homeostasis of dental pulp, hypoxia will inevitably induce the defensive reaction. However, this is a complex process and is regulated by numerous factors. In this study, we established an experimental animal model of orthodontic tooth movement to investigate the effects of mechanical force on the expression of VEGF and HIF-1α in dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…This may be explained due to the increased activity of odontoblasts, fibroblasts and odontoblast-like cells, involved in dentine production as a response to stimuli such as mastication, bruxism and occlusal trauma. This increased VEGFA expression in pulp tissue constitutes the mechanism to initiate new blood vessels formation (Roberts-Clark & Smith 2000, Ceradini & Gurtner 2005, Muz et al 2015, Wei et al 2015, Roth et al 2016, Caviedes-Bucheli et al 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained due to the increased activity of odontoblasts, fibroblasts and odontoblast-like cells, involved in dentine production as a response to stimuli such as mastication, bruxism and occlusal trauma. This increased VEGFA expression in pulp tissue constitutes the mechanism to initiate new blood vessels formation (Roberts-Clark & Smith 2000, Ceradini & Gurtner 2005, Muz et al 2015, Wei et al 2015, Roth et al 2016, Caviedes-Bucheli et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…VEGFR2 had similar expression in both groups, which could be explained by the vessels in the pulp tissue actively sprouting and these sprouts are dependent on the amount of VEGFR1 which has an inhibitor effect in the angiogenic process. (Roberts-Clark & Smith 2000, Mattuella et al 2007, Wei et al 2015, Rombouts et al 2016, Caviedes-Bucheli et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Franzen et al (20) applied 50 g force to move rats' first molars, and then removed the orthodontic appliances to study the periodontal tissue reaction to during orthodontic relapse in rats. Wei et al (22) used 30 g force to study the reaction of dental pulp tissues by examining HIF-1α and vascular endothelial growth factor; they revealed that the expression of HIF-1α was markedly increased in the 1, 3, 7 day and 2 week groups. In the present study, 50 g force was also applied between the maxillary right first molar and incisors of rats, and hypoxia-sensitive factor HIF-1α was highly expressed in PDL, which could also indicate that the model used was suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia describes the reduction of oxygen level in tissue due to decreased oxygen partial pressure beyond the physiologic level [5]. Hypoxic cells release cellular mediators, such as the hypoxia-inducible factor 1 (HIF-1), a heterodimer composed of HIF-1 and HIF-1 [6,7].…”
Section: Impact Of Hypoxia On Cellsmentioning
confidence: 99%